Reviewing Victimological Aspects and the Effectiveness of Legal Protection in Cases of Commercial Sexual Exploitation of Children - Rosyada, Rosa Auliya; Muhammad Arief Dwi Ramadhan; Sumali (Universitas Brawijaya, 2024)
This research is triggered by the rampant cases of commercial sexual exploitation of minors. Based on data from UNICEF, as many as 1,200,000 (one million two hundred thousand) children throughout the world are trafficked per year, with many factors causing this crime. Therefore, this research aims to examine in more depth the crime of commercial sexual exploitation of children by focusing on determining the victimological condition of the victim and also examining the effectiveness of legal protection against CSEC. This research method employs normative juridical research methods for collecting legal materials. Secondary legal sources were obtained by reviewing and studying various reference books, scientific articles and journals, while the primary ones referred to a statutory approach based on applicable laws and regulations and a case approach for criticising a case. With this research, it is hoped that the government can strive to protect CSEC victims through supervision, protection, prevention, treatment, rehabilitation, and a deterrent effect on the perpetrators. The role of international organisations is also needed to increase awareness and sensitisation of the community and children vulnerable to CSEC crimes and also as a way to help the victims' psychological recovery.